Designing constructed wetlands for reclamation of pretreated wastewater and stormwater - Tao, Wendong (2017)
Wastewater reclamation is getting greater attention as an alternative to conventional approaches to wastewater treatment and water supply due to increasing water stress coupled with more stringent water quality limitation for discharge of treated wastewater. Among the few technologies adopted in the field for wastewater reclamation, constructed wetlands have been used to reclaim both primary and secondary treated wastewater in regions with arid and humid climates. This paper summarizes the widely adopted guidelines that need to be considered when designing constructed wetlands for wastewater reclamation, discusses the capacity of wetland treatment systems for water reuse while assessing the status of full-scale constructed wetlands designed for wastewater reclamation, and develops contaminant loading charts as a design tool based on the performance of existing full-scale constructed wetlands deployed for wastewater reclamation. It is evident that constructed wetland systems provide a viable means to treat wastewater to the levels required for low-quality reuses such as restricted irrigation and impoundment. It is challenging for constructed wetlands to consistently meet microbiological guidelines for high-quality reuses such as unrestricted agricultural and urban reuses. Wastewater reclaimed through constructed wetlands is used mainly for agricultural and landscape irrigation, groundwater recharge, indirect potable reuse, and environmental reuse. Surface area and hydraulic loading rate of constructed wetlands to be deployed for wastewater reclamation can be estimated with contaminant loading charts derived from monitoring data of existing full-scale operations.